Regional Treatment Intensity as an Instrument for the Evaluation of Labour Market Policies - Markus Frölich; Michael Lechner (Institute for the Study of Labor (IZA), 2004)
The effects of active labour market policies (ALMP) on individual employment chances and earnings are evaluated by nonparametric instrumental variables based on Swiss administrative data with detailed regional information. Using an exogenous variation in the participation probabilities across fairly autonomous regional units (cantons) generated by the federal government, we identify the effects of ALMP by comparing individuals living in the same local labour market but in different cantons. Taking account of small sample problems occurring in IV estimation, our results suggest that ALMP increases individual employment probabilities by about 15% in the short term for a weighted subpopulation of compliers.
Keywords: C14; J68; 330; local average treatment effect; active labour market policy; state borders; geographic variation; weak instruments; small sample problems of IV; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Regionale Arbeitslosigkeit; Schätzung; Schweiz; treatment effect